2002
DOI: 10.1210/endo.143.3.8666
|View full text |Cite
|
Sign up to set email alerts
|

The Goitrogen 6-n-Propyl-2-Thiouracil (PTU) Given during Testis Development Increases Sertoli and Germ Cell Numbers per Cyst in Fish: The Tilapia (Oreochromis niloticus) Model

Abstract: The main objectives of the present study were to investigate the effects of 6-n-propyl-2-thiouracil (PTU) on Sertoli cell proliferation, germ cell number, and testis size in Nile tilapias (Oreochromis niloticus). In this regard, young fish (approximately 1 g BW and approximately 3.5 cm total in length) were treated for a period of 40 d with different concentrations (100 and 150 ppm) of PTU. The animals were killed and analyzed on d 1, 30, 40, 98, and 208 after the beginning of the treatment. On d 30 and 40 the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 14 publications
4
66
0
3
Order By: Relevance
“…A measurement of the nucleolar diameter of the Sertoli cell was important since it was observed that treatments could reduce it. Matta et al (2002) observed a reduction in the nucleolar diameter of this cell when they treated Nile tilapia with goitrogen drugs. Ko et al (1998) Kanamadi and Jirankali (1992) found around five spermatid cysts per tubule and as many primary spermatogonium and secondary spermatocide cysts.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A measurement of the nucleolar diameter of the Sertoli cell was important since it was observed that treatments could reduce it. Matta et al (2002) observed a reduction in the nucleolar diameter of this cell when they treated Nile tilapia with goitrogen drugs. Ko et al (1998) Kanamadi and Jirankali (1992) found around five spermatid cysts per tubule and as many primary spermatogonium and secondary spermatocide cysts.…”
Section: Discussionmentioning
confidence: 91%
“…The testes were fixed in 2.5% glutaraldehyde in 0.1M sodium phosphate buffer (pH 7.4) and included in glycol methacrylate (Historesin®, Reichert-Jung) following routine procedures. Serial longitudinal sections (3 µm and 4 µm) were obtained using rotary microtome (Reichert-Jung, Multicut® -2045) and glass razor, according to MATTA et al (2002). The sections were stained with 1% toluidine blue-sodium borate and mounted in Entellan® (Merck).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their well-established roles in influencing growth and morphology, THs have been shown to promote neural stem cell proliferation in the olfactory system of salmon indicating a role for THs in neurogenesis (Lema & Nevitt 2004), and to mediate the rheotactic shifts and migratory behaviors of salmon and other diadromous fishes (McCormick et al 1998, Edeline et al 2005. THs also appear to influence reproductive function in teleost fish, since inhibition of endogenous TH production during the time of gonadal germ cell differentiation leads to an increased density of Sertoli and germ cells per cyst in the testis (Matta et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…each Sertoli cell supports a certain, species-specific number of germ cells during spermatogenesis in 11 mammals and fish [15,29,33,41,25], the Sertoli cell number per testis ultimately dictates the 12 magnitude of testis size and sperm production [15,22,33]. In mammals, the pituitary gonadotropin 13 follicle-stimulating hormone (FSH) is a major stimulator of the proliferation of Sertoli cells [32,50], 14 until they attain a non-mitotic state during puberty [9,23].…”
mentioning
confidence: 99%